Combined Nurr1 and Foxa2 roles in the therapy of Parkinson's disease. Issue 5 (10th March 2015) - Oh, Sang‐Min; Chang, Mi‐Yoon; Song, Jae‐Jin; Rhee, Yong‐Hee; Joe, Eun‐Hye; Lee, Hyun‐Seob; Yi, Sang‐Hoon; Lee, Sang‐Hun
Abstract Use of the physiological mechanisms promoting midbrain DA (mDA) neuron survival seems an appropriate option for developing treatments for Parkinson's disease (PD). mDA neurons are specifically marked by expression of the transcription factors Nurr1 and Foxa2. We show herein that Nurr1 and Foxa2 interact to protect mDA neurons against various toxic insults, but their expression is lost during aging and degenerative processes. In addition to their proposed cell‐autonomous actions in mDA neurons, forced expression of these factors in neighboring glia synergistically protects degenerating mDA neurons in a paracrine mode. As a consequence of these bimodal actions, adeno‐associated virus (AAV)‐mediated gene delivery of Nurr1 and Foxa2 in a PD mouse model markedly protected mDA neurons and motor behaviors associated with nigrostriatal DA neurotransmission. The effects of the combined gene delivery were dramatic, highly reproducible, and sustained for at least 1 year, suggesting that expression of these factors is a promising approach in PD therapy.